Quantifying the forefoot bending stiffness of cleated American football shoes using the Football American Shoe Tester (FAST). (3rd May 2016) - Lessley, David J.; Crandall, Jeff; Frederick, Edward C.; Kent, Richard; Sherwood, Chris
Abstract : In American football, hyper-dorsiflexion of the first metatarsophalangeal (first MTP) joint is the predominant mechanism of first MTP joint sprains (turf toe). The risk of acute first MTP joint sprain has been found to increase as first MTP joint angle increases. The bending resistance of the shoe dictates the proportion of an externally applied load that can be passed into the shoe (i.e. not through the first MTP joint) and thus may influence the magnitude of flexion imparted to the first MTP joint and hence the risk of injury. The current study introduces the Football American Shoe Tester (FAST), a flexion apparatus designed to measure the bending resistance of American football shoes at angles of forefoot dorsiflexion from 15° to 75°. The FAST was used to quantify the forefoot bending behaviour of a range of American football shoes. Thirty different models of US size 12 shoes were tested. Linearized bending stiffness ranged from 0.27 to 0.8 Nm/deg, while peak torque ranged from 11.8 to 25.5 N m. The testing revealed characteristic differences in torque-angle response across shoe models and quantified the extent of shoe stiffening at angles of dorsiflexion beyond those studied in the past.